MANAJEMEN MUTU DALAM PERSPEKTIF ISLAM - Dian, Dian; Wahyuni, Anisa (Idaarah: Jurnal Manajemen Pendidikan, 2019)
This paper supports to explain the concept of quality management in Islamic perspective. Improvement efforts in simple educational institutions that are carried out continuous improvement. In order to produce quality educational outputs, the elements involved in education are also needed, competitive and efficient. Improving the quality of education is the first step that needs to be done. Quality must always get the attention and support of various parties. Therefore, quality management is needed in the development of professional Islamic educational institutions as an answer to these problems, especially in the context of educational autonomy today. For this reason, in order to improve the quality of Islamic educational institutions, they need to be assisted, defended, championed to be able to live and develop.